Study of crossability and F1 of interspecific hybridization between Brassica rapa (B. campestris) and B. nigra (Bangladesh Journal of Agricultural Research, 2008)
Interspecific hybridization between yellow seeded variety, Binasarisha-6 of B. rapa var. Yellow Sarson (2n=20; AA) and Nigra-1 of B. nigra (2n=16; BB) were made. The crosses with Binasarisha-6 of B. rapa var. Yellow Sarson as a female parent were only successful. Chromosome number in root tip cells of the F1 hybrids was 18, which was half of the sum total of the somatic chromosome number of the parents and indicated hybrid nature. Hybrids exhibited intermediate morphology between the parents. All the hybrids showed complete pollen sterility with shrivelled, pointed tip, and pale colour anthers and reduced filaments and failed to set siliquae and seeds.DOI: http://dx.doi.org/10.3329/bjar.v32i3.546Bangladesh J. Agril. Res. 32(3) : 445-449, September 2007